The postbiotic ReFerm® versus standard nutritional support in advanced alcohol-related liver disease (GALA-POSTBIO): a randomized controlled phase 2 trial - Johanne K. Hansen; Mads Israelsen; Suguru Nishijima; Sara E. Stinson; Peter Andersen; Stine Johansen; Camilla D. Hansen; Maximilian Joseph Brol; Sabine Klein; Robert Schierwagen; Frank Erhard Uschner; Karolina Sulek; et al. (Nature Communications)
Abstract Impaired gut barrier function may lead to progression of liver fibrosis in people with alcohol-related liver disease. The postbiotic ReFerm® can lower gut barrier permeability and may thereby  reduce fibrosis formation. Here, we report the results from an open-labelled, single centre randomized controlled trial where 56 patients with advanced, compensated, alcohol-related liver disease were assigned 1:1 to receive either ReFerm® (n = 28) or standard nutritional support (Fresubin®, n = 28) for 24 weeks. The primary outcome was a ≥ 10% reduction of the fibrosis formation marker alpha-smooth muscle actin in liver biopsies, assessed by a blinded pathologist using automated digital imaging analysis. Paired liver biopsies meeting quality criteria for the primary outcome were available for 40 participants (ReFerm®, n = 21 and Fresubin®, n = 19). This reduction was observed in 29% of patients receiving ReFerm®, compared to 14% with Fresubin® (OR = 2.40; 95% CI 0.63 to 9.16; p = 0.200). No treatment-related serious adverse events occurred. Our findings suggest that ReFerm® may reduce liver fibrosis by enhancing gut barrier function, potentially preventing the progression of alcohol-related liver disease.